Analysis of mechanical draft wet cooling towers - Mohiuddin, A. K. M.; Kant, Keshav (Regional Centre for Energy, Heat and Mass Transfer - for Asia and the Pacific, 1991)
The objective of the paper is to present a review on the analysis of mechanical-draft wet cooling towers. Starting with the basic fundamentals of a cooling tower, an attempt is made here to present an analysis of the important computational models available. The physical situation within a cooling tower is very complex (films and droplets of water in air are in a constantly changing configuration). There is no mathematical model which is capable of simulating every detail of simultaneous heat and mass transfer process occurring within the tower. Consequently, simplifying assumptions must be made for the analysis. A comprehensive list of assumptions is provided which are used for the different models. Eight computational models are analyzed here, namely (a) ESC code, (b) FACTS, (c) VERAZD, (d) STAR, (e) Sutherland's Model, (f) Model by Fujita and Tezuka, (g) Webb's Model, (h) Model by Jaber and Webb. Each model makes use of somewhat different set of assumptions. So, the results of the calculations of heat/mass transfer coefficients also differ. Analysis of the above models gives us an idea about different numerical solutions of cooling tower design. It is difficult to draw general conclusions concerning the comperative merits of the correlations, or of the codes. Yet it is attempted here to compare the different models from the view point of design, computational error, computational time, simplicity of usage and practicability.